ISLAMIC EDUCATION STRATEGIES IN FORMING STUDENT CHARACTER IN THE ERA OF INDUSTRIAL REOLUTION 4.0 - Aisyah, Ia Siti; Rahmatullah, Irfan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
In  the  4.0  era,  the  formation  of  student  character  is  very  important  because technological progress  is  unstoppable  and  information  can  spread  quickly. This research aims to find out how Islamic education strategies shape student character in the era of revolution 4.0. The research method used is descriptive with  a  qualitative-phenomenological  approach.  Data  analysis  uses  Miles  and Huberman's  interactive  model  through  four  stages,  which  include:  data collection,  data  reduction,  data  presentation,  and  drawing  conclusions.  The research results show that student character formation can be integrated with learning,  example,  a  good  environment,  and  habituation  which  is  closely related to character education. To build the character of his students, a teacher must  be  an  example  for  his  students.  Apart  from  that,  Islamic  religious education  contributes  to the  formation  of  students'  character  through  the following  activities:  (1)  Intracurricular  activities:  In  these  activities,  teachers incorporate  character  into  the  lessons  of  each  subject,  such  as  the  Qur'an, Hadith, Fiqh, Islamic Cultural History, Arabic Language, and Moral Creeds. In this  activity,  the  teacher  is  directly  connected  to  the  material  on  morality  or character.  (2)  Extracurricular  activities:  Tilawati  Several  traits  are  built through  these  two  types  of  activities:  religious,  honest,  likes  to read, responsible, independent, appreciates achievements, cares socially, and works hard.  The  students  are  ready  to  face  the  industrial  era  4.0  with  character. Islamic character will be formed by good cooperation between schools, parents and the community